Prophylactic Effects of Bifidobacterium adolescentis on Anxiety and Depression-Like Phenotypes After Chronic Stress: A Role of the Gut Microbiota-Inflammation Axis - Guo, Ying; Xie, Jian-Ping; Deng, Ke; Li, Xia; Yuan, Yun; Xuan, Qun; Xie, Jing; He, Xiao-Ming; Wang, Qian; Li, Juan-Juan; Luo, Huai-Rong (Frontiers in Behavioral Neuroscience, 2019)
Stresses disturb the balance of gut microbiota, and stimulate the inflammation-to-brain mechanisms together with anxious and depressive disorders. Bifidobacterium adolescentis displayed distinct anti-inflammatory effects, however no research has focused on the anxiolytic and antidepressant effects of B. adolescentis on chronic restraint stress mice, and the inflammatory mechanisms related to gut microbiome have not yet been expounded. We found that the pretreatment with B. adolescentis increased the time in the center of open field test as well as entries in open arms of elevated plus-maze test, and decreased immobility duration in tail suspension test as well as forced swimming test. Moreover, B. adolescentis increased the sequences proportion of Lactobacillus, and reduced the sequences proportion of Bacteroides in faeces. Furthermore, B. adolescentis remarkably reduced protein expression of IL-1β, TNF-α, p-NF-κ B p65 as well as Iba1, and elevated BDNF expression in hippocampus. We concluded that the anxiolytic and antidepressant effects of B. adolescentis were related to reducing inflammatory cytokines and rebalancing the gut microbiota.